Japan's economic structure should it change? (Society for Japanese Studies, 1990)
Will Japan's economic structure change? confessions of a former optimist; The U. S. - Japan trade problem an economic analysis from a Japanese viewpoint; Trade, revisionism and the rule of law the nature of the trade conflict and the American reponse,....